Using the EPOSTL for Dialogic Reflection in EFL Teacher Education - Schauber, Holli (GIST – Education and Learning Research Journal, 2015)
For many pre-service English as a Foreign Language (EFL) teachers and their mentors, the theory and practice driven European Portfolio for Student Teachers of Languages (EPOSTL)3 occupies a prominent and practical role in their preparation programs as a delivery system of core pedagogical skills and knowledge. Interest in the role that dialogical reflection plays in this process is studied in an EFL teacher education program at a Swiss university that relies heavily on the EPOSTL for the professional development awareness-raising. While the EPOSTL contributes valuable core knowledge to the processes of dialogic and mentored-reflection, certain program components provide more opportunities for scaffolded reflection than others.